Association Between Life’s Essential 8 and Frailty in Adults with Asthma - Jiao Xu; Min Zhang (Dose-Response)
Objectives To investigate the correlation between Life’s Essential 8 (LE8) and frailty in adults with asthma using data from National Health and Nutrition Examination Survey (NHANES). Methods We conducted a cross-sectional study by NHANES data (2001-2018) to assess the relationship between LE8 and frailty in asthma patients. Multiple logistic regression, restricted cubic spline (RCS) analysis, and subgroup analyses were performed to evaluate potential associations. Results Among the 3, 238 of 91 351 participants, 1066 asthma patients demonstrated frailty and 2172 asthma patients not. When comparing the groups with moderate and high LE8 scores to the group with low LE8 scores, the odds ratios (ORs) (95% confidence intervals) for frailty in asthma were 0.39 (0.27, 0.56) and 0.15 (0.08, 0.27),respectively. Every 10-point increment of LE8 scores was negatively correlated with frailty in asthma. Similar trends were observed for health behavior and health factor scores. ORs for frailty in asthma were 0.54 (0.41, 0.72) and 0.41(0.27, 0.64) when comparing the groups with moderate and high health behavior scores to the group with low health behavior scores. ORs for frailty in asthma were 0.68 (0.48, 0.98) and 0.50 (0.28, 0.88) when comparing the groups with moderate and high health factor scores to the group with low health factor scores. ORs for frailty in asthma were 0.78 (0.72, 0.84) both in the every 10-point increment of health behavior and health factor scores. Conclusions Higher LE8 scores, along with health behavior and health factor scores, were linearly and inversely associated with the prevalence frailty in adults with asthma, suggesting that improved LE8 may reduce frailty risk in asthma population.